Pengembangan Media Pembelajaran Interaktif Berbasis PPT untuk Meningkatkan Hasil Belajar IPS Materi Perubahan Sosial Budaya dan Globalisasi Di SMP Negeri 3 Kroya - Ahmad Dahlan; Sriyanto Sriyanto (UM Purwokerto Press, 2022)
This research was conducted because teachers need ICT-based learning media, namely interactive PowerPoint adapted to the KTSP, to be used in the learning process. The purpose of this study was to develop a learning media in the form of interactive PowerPoint for class IX in social studies subject matter of Socio-Cultural Change and Globalization at SMP Negeri 3 Kroya Kab. Cilacap. This type of research is research and development. This study uses a nine-step development research procedure proposed by Borg and Gall, namely: 1) potential and problems, 2) data collection, 3) product design, 4) design validation, 5) design revision, 6) product trials, 7 ) product revision, 8) use trial, and 9) product revision which will then become the final product in the form of interactive PowerPoint learning media for class IX students of SMP Negeri 3 Kroya. The subjects in this study were students of class IX SMP Negeri 3 Kroya. The instruments used in this study were a list of interview questions and questionnaires. The list of questions is used to conduct a needs analysis of subject teachers at SMP Negeri 3 Kroya. Questionnaires were used to validate the interactive PowerPoint learning media conducted by two learning media experts and two social studies teachers.